234k views
0 votes
Look at the system of equations below
Sy= -2x +3
1 4x – 3y = 11

Look at the system of equations below Sy= -2x +3 1 4x – 3y = 11-example-1
User Karan Vs
by
6.0k points

1 Answer

6 votes

Answer:

(2,-1)

y= -1

x= 2

Explanation:

y= -2x+3

4x-3y=11

substitute the value of y into an equation

4x-3(-2x+3)=11

distribute by multiplying numbers in parenthesis by -3

4x+6x-9=11

add 4x to 6x

10x-9=11

add 9 from both sides

10x=20

divide both sides by 10

x=2

substitute the value of x into an equation

y= -2•2+3

multiply -2 to 2

y= -4+3

add -4 to 3 but 4 is negative, so subtract

y= -1

-----------

(2,-1)

-----------

User Fernando Vezzali
by
6.9k points